PERANCANGAN INTERNET OF THINGS PADA PROTOTIPE PLTMH AIR TERJUN DESA LES - Guna Winangun, Nyoman Gede Resa; Putri Siswanto, Fagita; Putra Winaya, Ida Bagus; Gunantara, Nyoman; Sukerayasa, I Wayan; Arsa Suyadnya, I Made (Jurnal SPEKTRUM; Vol 11 No 4 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i04.p7, 2024)
Les Village is famous for its natural attractions. Nature tourism in Les Village, especially Les Waterfall, has a lot of potential, one of which is water flow as a driving source for a Micro Hydro Power Plant. In addition to its great potential as a source of generation, as a tourist area, Les Waterfall is quite deep into the forest so that if an MHP is built it is quite difficult to conduct direct monitoring. Through a prototype made with a size 4 times smaller than the size it should be, an Internet of Things design was made with the aim of being able to monitor the performance of an MHP anywhere and anytime as long as it has an internet connection. The IoT itself is designed using the PZEM-017 sensor which is connected to the ESP8266 as a data sender to Blynk. With this prototype, the maximum voltage produced is 10.3 Volts with a current of 0.10 Ampere. The data can already be displayed with Blynk Console for lay users to be easily understood.